Psychological Symptoms as Predictors of Organizational Conflict Among Bankers - Abamara, Chukwudum Nnaemeka; Anazodo, Nkechi Nneamaka; Onyekaba, Onyinye C; Onyemaechi, Chinwe (Practicum Psychologia, 2018)
This study investigated psychological symptoms (depressive symptoms, anxiety and paranoid ideation) as predictors of organizational conflict. A total of 157 male and female bankers from five different banks in Onitsha participated in the study. A structured questionnaire form containing four validated scales of measurement namely; depressive symptoms scale, anxiety scale, paranoid ideation scale and organizational conflict scale were used as instr ment for the study. Regression statistics was adopted as a statistical tool for data analysis. The results indicated that depression significantly and independently predict organizational conflict among bankers (B= .81; t=20.71, p<.05); anxiety did not significantly predict organizational conflict among bankers (B=.06; t=1.41, p>.05); and paranoid ideation did not significantly predict organizational conflict among bankers (B= - .00; t=-.07, P>.05). Based on the above findings, this study concluded that depressive symptoms is positively related to organizational conflict among bankers, while anxiety and paranoid ideation may not be among the significant predictors of organizational conflict